Analisis Pengendalian Kualitas Daging Kepiting Rajungan dengan Pendekatan Seven Tools - Rosyidi, Moh Ririn; Izzah, Nailul (LPPM Universitas Bina Sarana Informatika, 2025)
Miniplant, UMKM Roby Jaya is a seafood processing company that has quality control issues due to product defect levels. The purpose of this study is to identify the most common types of faults, investigate the causes, and suggest improvement measures to improve production quality. The Seven Tools technique was employed in this study, which included check sheets, flowcharts, pareto diagrams, histograms, scatter diagrams, control charts, and fishbone diagrams, while the 5W + 1H concept was used to develop improvement proposals. The investigation revealed that the most common forms of flaws were broken meat (72.31%) and unclean meat (27.69%), with humans, the environment, materials, and production procedures serving as the primary causes. To improve product quality, the organization should raise employee labor effectiveness, optimize the production process, and conduct periodic evaluations.